Management and assessment of the built heritage in the Historic Centre of Callao - Montañez Arica, Marsia (2016)
A historic centre has an important meaning for the local community. Its preservation cannot be isolated from its physical and social context nor ignore the city’s urban development. Therefore, collaborative actions and the participation of all social stakeholders involved are crucial. This complex situation requires suitable management approaches. In regard to the Historic Centre of Callao (Peru), where the built heritage is in a precarious situation, abandoned or demolished, there are issues concerning its preservation. This paper examines the relationship between its state of preservation in 2015, and management processes and tools that help identify heritage values. The analysis shows there is a lack of cultural heritage identification and protection processes that complement existing legal provisions. It also demonstrates the poor coordination and communication between the public dependencies in charge of built heritage.